Excavations at four prehistoric rock carvings on the Ben Lawers Estate, 2007–2010 - Bradley, Richard; Watson, Aaron; Anderson-Whymark, Hugo; Stewart, Rosemary; Brown, Alex (Proceedings of the Society of Antiquaries of Scotland, 2013)
How were Neolithic rock carvings related to the areas around them? Were they associated with structures or deposits of artefacts, and did that relationship differ between landscapes with earlier prehistoric monuments, and places where they were absent? This paper discusses the results of excavation around four decorated surfaces at All Coire Phadairlidh on the National Trust for Scotland's Ben Lawers Estate. They are compared with fieldwork around two conspicuous rocks on the same site, neither of which had been carved. No monuments were present in the vicinity, although there was a 'natural' standing stone. Excavation showed that all the decorated surfaces were associated with deposits of artefact, some of them on top of the rocks and others at their base. The more complex carvings were associated with the largest collections, and the control sample of undecorated rocks was not associated with any finds. The excavated material included two pieces of Arran pitchstone, a worked flint, a beach pebble, and a substantial quantity of broken and flaked quartz. One of the decorated outcrops was associated with an area of cobbles containing a number of artefacts. Fossil pollen sealed by this deposit suggested that the surrounding area was used as upland pasture; similar evidence was obtained from another rock carving at Tombr3eck, 5 km away. Some of the fragments of broken quartz were parts of broken hammerstones, but the distribution of these pieces showed little relationship to the hardness of the rocks where they were found, or the extent of the associated carvings. On the other hand it was closely related to the composition of the stone. Carvings on epidiorite were not associated with many artefacts, but that did not apply to those created on mica schist which glitters in the sun and even in moonlight. It may be that these surfaces of these stones had been prepared by pecking or hammering in order to enhance this effect. If so, the selection of particular rocks for special attention may have been as important as the designs that were created there.